La extinción de la relación laboral por causas relacionadas con la capacidad del trabajador - Cadillo Ángeles, Carlos (Revista de Derecho, 2019)
The present article deals with the causes for the extinction of work relationship basedon the affectation of the worker’s abilities: Permanent absolute handicap and dismissalrelated to ability. The latter gathers three postulations: deficiencies in the worker’s abilities,deficient performance, and refusal to undertake medical examinations or to complywith prophylactic or healing measures prescribed by the doctor with preventive aims.These are all issues of upmost importance which even when they justify the breaking ofthe work relationship, limit the worker’s work stability. In this regards, we develop thescope, requisites and formalities which should be met for a justified usage of such causal.
Keywords: Permanent absolute handicap; dismissal because of ability; deficiencies in ability; deficient performance